A nationwide evaluation of bevacizumab-based treatments in pediatric low-grade glioma in the UK: Safety, efficacy, visual morbidity, and outcomes. Issue 4 (14th October 2022) - Green, Katherine; Panagopoulou, Paraskevi; D'Arco, Felice; O'Hare, Patricia; Bowman, Richard; Walters, Bronwen; Dahl, Christine; Jorgensen, Mette; Patel, Pritesh; Slater, Olga; Ahmed, Rehana; Bailey, Simon; et al.
Abstract: Background: Bevacizumab is increasingly used in children with pediatric low-grade glioma (PLGG) despite limited evidence. A nationwide UK service evaluation was conducted to provide larger cohort "real life" safety and efficacy data including functional visual outcomes. Methods: Children receiving bevacizumab-based treatments (BBT) for PLGG (2009–2020) from 11 centers were included. Standardized neuro-radiological (RANO-LGG) and visual (logMAR visual acuity) criteria were used to assess clinical–radiological correlation, survival outcomes and multivariate prognostic analysis. Results: Eighty-eight children with PLGG received BBT either as 3rd line with irinotecan (85%) or alongside 1st/2nd line chemotherapies (15%). Toxicity was limited and minimal. Partial response (PR, 40%), stable disease (SD, 49%), and progressive disease (PD, 11%) were seen during BBT. However, 65% progressed at 8 months (median) from BBT cessation, leading to a radiology-based 3 yr-progression-free survival (PFS) of 29%. Diencephalic syndrome ( P = .03) was associated with adverse PFS. Pre-existing visual morbidity included unilateral (25%) or bilateral (11%) blindness. Improvement (29%) or stabilization (49%) of visual acuity was achieved, more often in patients' best eyes. Vision deteriorated during BBT in 14 (22%), with 3-year visual-PFS of 53%; more often in patients' worst eyes. A superior visual outcome ( P = .023) was seen in neurofibromatosis type 1-associated optic pathway glioma (OPG). Concordance between visual and radiological responses was 36%; optimized to 48% using only best eye responses. Conclusions: BBTs provide effective short-term PLGG control and delay further progression, with a better sustained visual (best > worst eye) than radiological response. Further research could optimize the role of BBT toward a potentially sight-saving strategy in OPG.